Determination of genetic diversity in persimmon accessions using morphological and inter simple sequence repeat markers - Yazgan Tunç; Canan Aydınlıoğlu; Kadir Uğurtan Yılmaz; Ali Khadivi; Daya Shankar Mishra; El Hassan Sakar; Tomáš Vyhnánek (Scientific Reports)
Abstract Background: Persimmon (Diospyros kaki L.) belongs to the Ebenaceae family, which includes six genera and about 400 species. This study evaluated the genetic diversity of 100 persimmon accessions from Hatay province, Türkiye using 42 morphological and pomological traits, along with inter simple sequence repeat (ISSR) markers and multivariate analysis. Results: Statistical analysis revealed significant differences among the accessions (ANOVA, p < 0.05). The coefficient of variation ranged from 19.24% for leaf length to 133.89% for fruit calyx groove end, with 97.62% of traits showing more than 20% variation. This indicates high genetic variability. Fruit weight, length, and diameter varied greatly, with strong positive correlations between fruit weight and other traits. Principal component analysis explained 72.42% of the total variance, while cluster analysis showed varying levels of similarity among accessions. ISSR analysis identified 139 bands, 128 of which were polymorphic. The similarity index ranged from 0.41 to 0.96. Notably, accessions ‘P78’, ‘P7’, ‘P48’, ‘P29’, ‘P44’, ‘P25’, ‘P5’, ‘P98’, ‘P80’, ‘P50’, ‘P37’, ‘P77’, ‘P57’, ‘P56’, ‘P41’, ‘P73’, ‘P39’, ‘P65’, ‘P72’, and ‘P61’ were identified as promising candidates for further study. Conclusions: This study demonstrates significant genetic diversity in persimmon accessions from Hatay. The high variability supports adaptability and resilience. Positive correlations among traits, especially fruit weight, are useful for breeding. ISSR markers highlighted valuable polymorphic bands, underlining the importance of local germplasm for developing resilient cultivars. Variations in growth vigor and ripening dates offer opportunities for customized cultivation practices, contributing to sustainable agriculture.